On Democratic Reason. Issue 1 (27th February 2019) - Katznelson, Ira
Abstract : Our responsibilities for democracy are sharper, more demanding than at any time since my childhood. If we are to renew democracy and secure knowledge, policy schools, as Helmut Anheier insists, must advance democratic policy reason with clarity, dedication, and purpose.